Deregulation of RBP4 and RBP7 Genes in Clear Cell Renal Cell Carcinoma - Kudryavtseva, Anna Viktorovna (Asian Journal of Pharmaceutics (AJP), 2017)
Background: The incidence of clear cell renal cell carcinoma (ccRCC) steadily increases each year, while the molecular mechanisms involved in the initiation and progression of the disease remain unclear. Therefore, the search for genes that could be potential targets for therapy as well as diagnostic and prognostic markers is an important task. In this work, we studied the expression of genes, encoding retinol binding proteins, in ccRCC. Materials and Methods: Using quantitative polymerase chain reaction, we analyzed the expression of RBP2, RBP4, and RBP7 genes in a representative set of ccRCC samples. Results: We identified deregulation of RPB4 and RBP7 genes in ccRCC. Significant decrease in the expression of the RBP4 gene was shown in most ccRCC samples. In contrast, the increase in mRNA level of the RBP7 gene was observed in almost all cases. Conclusions: Obtained results allow us to assume that RBP4 and RBP7 could be involved in ccRCC carcinogenesis. Moreover, our data confirm alterations in retinoid metabolism in ccRCC.